Implementation of QR Payment on Android-Based Waste Banks - Sabana Nur Rizki Hermawan; Abdul Azis (Politeknik Piksi Ganesha Indonesia, 2024)
This research aims to implement a QR Payment system as an effort to increase attractiveness and encourage greater community participation in waste management at KSM BIMA, facilitating transactions, particularly the exchange of customer points for goods. The analytical method employed in this research is Design Thinking. The results demonstrate the successful implementation of the QR Payment system in the Android application of KSM BIMA waste bank. The prototype creation involved three stages: the first stage for developing an Android application prototype for customers and administrators, the second stage for QR Payment system development and creating Android applications for partners, and the final stage for adding several program features to the QR Payment system, setting an age limit for point redemption and generating reports for each application. Testing using the Black Box Testing method indicates that the implemented system functions effectively.